THE RELEVANCE OF MODERN PROBLEMS OF RESTORATION AND THEORETICAL FOUNDATIONS OF RESTORATION AND RECONSTRUCTION - Ass. prof. Tigin To”re; Associate Professor Talipova N. Z.; Assoc. Prof. Omonova D. F.; Associate Professor Kadabaeva Sh. S. (Journals Park Publishing, 2024)
The article presents analytical information about the methodological system of the restoration process and the theoretical model of restoration.
Keywords: Restoration of buildings and structures, historical and architectural monuments, cultural heritage sites, methodology of the restoration process, optimal theoretical model of restoration.